Manajemen Persediaan Tepung Terigu dengan Metode Economic Order Quantity (EOQ) pada Perusahaan Roti Nikki Echo Payakumbuh - Desi Rahma Yani; Mega Amelia Putri; John Nefri (Politeknik Pertanian Negeri Payakumbuh, 2018)
Inventory management has an important role in a company because inventory management can decrease production cost. Economic order quantity using to minimize the production cost. Inventory management of flour in bread company Nikki Echo not been seen clearly prove by so many booking amount. It can giving addition of cost. The purpose of this research is (1) Analyzing optimal flour stock by using EOQ method in bread company Nikki Echo, (2) Analyzing reorder point raw material inventory by using EOQ method in bread company Nikki Echo, (3) Analyzing total raw material inventory cost by using EOQ method in bread company Nikki Echo. This research be held from February 20 until April 19 2018 in bread company Nikki Echo, Tanjung Pauh, Payakumbuh city, West Sumatera province. Flour stock by using EOQ method as much 17.394 kg it means the amount greater than company policy. That amount increase 79,6percents from the amount set by company. Frequency of booking less than company policy that is 7 times booking. Amount of reorder by using EOQ method is 10.251 kg with the inventory lead time for 3 days. Total inventory cost by using EOQ method as many Rp 11.445.513. This value small than total inventory cost issued by company policy. Decreasing cost amount 98percents from company policy. That cause by ordering amount reduced 33 times or same with 82,5percents from the amount before